Human Lung Microbiome on the Way to Cancer. (29th July 2019) - Kovaleva, Olga V.; Romashin, Daniil; Zborovskaya, Irina B.; Davydov, Mikhail M.; Shogenov, Murat S.; Gratchev, Alexei
Abstract : Recent research on cancer-associated microbial communities led to the accumulation of data on the interplay between bacteria, immune and tumor cells, the pathways of bacterial induction of carcinogenesis, and its meaningfulness for medicine. Microbial communities that have any kind of impact on tumor progression and microorganisms associated with tumors have been defined as oncobiome. Over the last decades, a number of studies were dedicated to Helicobacter pylori and its role in the progression of stomach tumors, so this correlation can be regarded as proven. Involvement of bacteria in the induction of lung cancer has been largely ignored for a long time, though some correlations between this type of cancer and lung microbiome were established. Despite the fact that in the present the microbial impact on lung cancer progression has many confirmations, the underlying mechanisms are poorly understood. Microorganisms can contribute to tumor initiation and progression through production of bacteriotoxins and other proinflammatory factors. The purpose of this review is to organize the available data on lung cancer microbiome and its role in malignant tumor progression.